Effect of X-ray diagnostic energy to peripheral blood mononuclear cells and CD34+/CD133+ expression: an in vitro study - Moonkum, Nutthapong; Wongpiem, Umpolprot; Sriwongta, Soontaree; Danthanawat, Nuttapong; Tochaikul, Gunjanaporn; Pilapong, Chalermchai (Journal of Current Science and Technology, 2021)
X-rays are high-energy waves that have a great ability to penetrate other materials. For that reason, X-rays are often used in medical applications to diagnose and treat cancer. There are many benefits for patients from medical imaging but X-rays can damage the cells in human body. The aim of this research was to study the effects of diagnostic X-rays on peripheral blood mononuclear cells (PBMCs) and CD34+/CD133+ populations in healthy volunteers in vitro and determine the ratio of CD34+/CD133+ in PBMCs. The PBMCs were isolated by ficoll-centrifugation technique. The morphology and CD34+/CD133+ expression of PBMCs were observed by inverted microscope and flow cytometry at 1 hr, 1, 5, 10, and 15 days after irradiation based on plain film x-ray technique of 70-110 kVp, 5-40 mAs, and radiation dose of 0.47-2.30 mGy. Freshly isolated PBMCs were spherical and after X-ray irradiation at day 15 revealed that the morphology was similar in both groups and the CD34+/CD133+ expression showed no difference from control when using the lowest radiation dose at 0.47 mGy. The overall results indicated that increasing the radiation dose had significant effects on PBMCs and the CD34+/CD133+ population of cells. Despite these negative effects, the benefits of radiation to both workers and patients outweigh the drawbacks.